การวิเคราะห์พฤติกรรมการแทรกตัวและคุณลักษณะของ ยานพาหนะสำหรับพัฒนาแบบจำลองการจราจร ระดับจุลภาคในพื้นที่เมืองเชียงใหม่ - กรณ์ ยะมัง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Microscopic Traffic Simulation used for designing and evaluating the performance of road infrastructure and facilities. It is an effective and widely accepted method. Moreover, traffic simulation is reasonable and consistent with the actual traffic conditions. It is necessary to study the specific driving behaviors and vehicle characteristics in the study area, for reducing the errors that may occur by the default value from the simulations. This research aims to (1) modify the driving behavior of vehicles and collecting vehicle characteristics data as a database; and (2) developing the microscopic simulation models as the actual traffic conditions in the road network in the Chiang Mai urban area. The collected data consists of 2 categories, which are Kinematic characteristics of vehicles and Static characteristics of vehicles. They are the essential parameters that affect traffic efficiency on the road network. This research uses the modified driving behavior and vehicle characteristics to create a vehicle movement model in the microscopic simulation, which can be divided into two main conditions - the default and the modified motorcycle driving behavior. After that, evaluate the traffic performance by using density, queue length, and road capacity. The results of performance evaluation found that the modified model increase density in all three intersections. Due to the behavior of driving behind, in which the parameters that affect the most density is the average distance from the vehicles in front (Average standstill distance). Moreover, the queue length has decreased. As for the capacity evaluation of all three intersections, It found that the capacity of the modified simulation is higher than the default.